An enzyme-based reversible Controlled NOT (CNOT) logic gate operating on a semiconductor transducer. (December 2017) - Honarvarfard, Elham; Gamella, Maria; Poghossian, Arshak; Schöning, Michael J.; Katz, Evgeny
Graphical abstract: Abstract: An enzyme-based biocatalytic system mimicking operation of a logically reversible Controlled NOT (CNOT) gate has been interfaced with semiconductor electronic transducers. Electrolyte–insulator–semiconductor (EIS) structures have been used to transduce chemical changes produced by the enzyme system to an electronically readable capacitive output signal using field-effect features of the EIS device. Two enzymes, urease and esterase, were immobilized on the insulating interface of EIS structure producing local pH changes performing XOR logic operation controlled by various combinations of the input signals represented by urea and ethyl butyrate. Another EIS transducer was functionalized with esterase only, thus performing Identity (ID) logic operation for the ethyl butyrate input. Both semiconductor devices assembled in parallel operated as a logically reversible CNOT gate. The present system, despite its simplicity, demonstrated for the first time logically reversible function of the enzyme system transduced electronically with the semiconductor devices. The biomolecular realization of a CNOT gate interfaced with semiconductors is promising for integration into complex biomolecular networks and future biosensor/biomedical applications.